2016
DOI: 10.7287/peerj.preprints.1701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of weight controllability beliefs on prejudice and self-efficacy

Abstract: An experiment was conducted to test for the presence of prejudice towards obesity and whether weight controllability beliefs information reduces this prejudice and impacts on a person's own healthy eating self-efficacy. The experiment randomly allocated 346 participants (49 males) into one of three conditions: controllable contributors toward obesity condition (e.g., information about personal control about diet and exercise); uncontrollable contributors toward obesity condition (e.g., information about genes,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Preliminary evidence suggests that the relationship between incremental theories of weight and stigma is complicated. For example, a recent study showed no effect of an incremental weight message on anti‐fat prejudice compared to a control condition (Thorsteinsson, Loi, & Breadsell, ). This lack of direct effect might be explained by new work illustrating a double‐edged sword effect of incremental theories of weight on fat stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence suggests that the relationship between incremental theories of weight and stigma is complicated. For example, a recent study showed no effect of an incremental weight message on anti‐fat prejudice compared to a control condition (Thorsteinsson, Loi, & Breadsell, ). This lack of direct effect might be explained by new work illustrating a double‐edged sword effect of incremental theories of weight on fat stigma.…”
Section: Discussionmentioning
confidence: 99%
“…First, the first perspective – weight is controllable – is by and far the most dominant perspective. The consequences, then, become critical to document: controllability of body size (and blame on the larger‐bodied person) predicts feelings of disgust, bias, dislike, even hatred towards a larger‐bodied person (Black et al., 2014; Ksinan, Almenara, & Vaculik, 2017; Puhl & Liu, 2015; Saguy & Riley, 2005; Thorsteinsson, Loi, & Breadsell, 2016). The dual frames of healthism and controllability may help researchers break down an observer’s decision‐making process as they process these common emotions about larger‐bodied colleague, such as examining what prompts an emotion of disgust to transform into an action of incivility towards a larger‐bodied colleague.…”
Section: Foreground: Weight‐based Stigma Through the Lens Of Objectif...mentioning
confidence: 99%